Excisional Goniotomy in Latino Patients with Open-Angle Glaucoma: Outcomes Through 24 Months - Porter M (Dove Medical Press, 2020)
Matthew Porter,1,2 Arnulfo Garza,3 Mark Gallardo1 1Private Practice, El Paso Eye Surgeons, P.A., El Paso, Texas, USA; 2Texas Tech University Health Sciences Center School of Medicine-Lubbock, Lubbock, TX, USA; 3Texas Tech University Paul L. Foster School of Medicine, Lubbock, TX, USACorrespondence: Mark Gallardo Private Practice, El Paso Eye Surgeons, P.A., 1201 N. Mesa, Ste G, El Paso, TX 79902, USAEmail gallardomark@hotmail.comPurpose: To characterize the efficacy of combined phacoemulsification and excisional goniotomy with the Kahook Dual Blade (KDB-phaco) in eyes of Latino adults with cataract and open-angle glaucoma (OAG).Methods: Health records of consecutive Latino patients undergoing KDB-phaco were retrospectively reviewed. Intraocular pressure (IOP) and IOP-lowering medication use were recorded at baseline and each postoperative visit through up to 24 months. Primary outcomes were reductions in IOP and medication use from baseline; secondary outcomes were the proportions of eyes achieving IOP reductions of ≥ 20% and medication reductions ≥ 1 medication from baseline. Subgroup analysis was conducted in eyes with high and low baseline IOP.Results: Data from 44 eyes of 32 Latino patients with OAG were analyzed. Mean IOP was 17.8 (0.7) mmHg at baseline and postoperatively ranged from 12.4 to 13.8 mmHg (p≥ 0.0003), representing mean IOP reductions of 4.2– 4.6 mmHg (19.7– 23.1%). Mean medication was 1.5 (0.2) medications per eye at baseline and postoperatively ranged from 0.2 to 1.0 (p≥ 0.0061), representing mean medication reductions of 0.7– 1.2 medications per eye (47.1– 87.2%). In the low baseline IOP group (< 18 mmHg), mean IOP was significantly reduced through Month 24 and medications through Month 12; in the high baseline IOP group (≥ 18 mmHg), IOP and medications were significantly reduced through Month 24. From Months 1– 24, IOP reductions of ≥ 20% were achieved by 48.4– 56.2% of eyes in the full cohort, by 20.0– 33.3% in the low IOP group, and by 66.7– 100% in the high IOP group; medication reductions of ≥ 1 medication were achieved by 72.0– 95.6%, 64.7– 94.2%, and 87.5– 100% of eyes, respectively.Conclusion: Combined KDB-phaco in eyes of Latino patients with glaucoma and cataract significantly lowers IOP and the need for IOP-lowering medications for up to 24 months and should be considered for such patients who warrant IOP reduction, medication reduction, or both.Keywords: glaucoma, intraocular pressure, excisional goniotomy, Kahook Dual Blade, Latino